Contractile Activity Regulates Inducible Nitric Oxide Synthase Expression and NOi Production in Cardiomyocytes via a FAK-Dependent Signaling Pathway. (26th July 2012) - Chu, Miensheng; Koshman, Yevgeniya; Iyengar, Rekha; Kim, Taehoon; Russell, Brenda; Samarel, Allen M.
Abstract : Intracellular nitric oxide (NO i ) is a physiological regulator of excitation-contraction coupling, but is also involved in the development of cardiac dysfunction during hypertrophy and heart failure. To determine whether contractile activity regulates nitric oxide synthase (NOS) expression, spontaneously contracting, neonatal rat ventricular myocytes (NRVM) were treat with L-type calcium channel blockers (nifedipine and verapamil) or myosin II ATPase inhibitors (butanedione monoxime (BDM) and blebbistatin) to produce contractile arrest. Both types of inhibitors significantly reduced iNOS but not eNOS expression, and also reduced NO i production. Inhibiting contractile activity also reduced focal adhesion kinase (FAK) and AKT phosphorylation. Contraction-induced iNOS expression required FAK and phosphatidylinositol 3-kinase (PI(3)K), as both PF573228 and LY294002 (10 μ M, 24 h) eliminated contraction-induced iNOS expression. Similarly, shRNAs specific for FAK (shFAK) caused FAK knockdown, reduced AKT phosphorylation at T308 and S473, and reduced iNOS expression. In contrast, shRNA-mediated knockdown of PYK2, the other member of the FAK-family of protein tyrosine kinases, had much less of an effect. Conversely, overexpression of a constitutively active form of FAK (CD2-FAK) or AKT (Myr-AKT) reversed the inhibitory effect of BDM on iNOS expression and NO i production. Thus, contraction-induced iNOS expression and NO i production in NRVM are mediated via a FAK-PI(3)K-AKT signaling pathway.